Wielki wiec wyborczy. (Gdańsk : [s.n.], 1947)
Afisz inf. o wiecu wyborczym, który miał miejsce 4.01.1947 r.
Keywords: Kwiatkowski, Eugeniusz -- (1888-1974).; Stocznia Gdańska -- 1945-1970 -- druki ulotne; Wybory -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- polityka i rządy -- 1945-1970 -- źródła; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- źródła